(untitled) (Research, Society and Development, 2020)
Open markets stand out for selling fresh products of animal and vegetable origin, most of the time free of pesticides. However, the failure to apply the good practices provided for by legislation that guarantee the quality and safety of food, can interfere with the sensory characteristics of the product offered, and linked to these factors, open markets can offer food with reduced quality, resulting in waste, monetary losses and deposits of these residues in the environment. This article aims to assess quality control in the trade of fruits and vegetables sold at Feira Livre in Valença / RJ. This was a descriptive observational study, based on Resolutions RDC n°. 216/2004, RDC n°. 275/2002, Ordinance MS n°. 326/1997, and Ordinance MS n°. 1428/1993. It was possible to observe, that the marketers had the minimum knowledge about the good practices, hygiene and conservation of the vegetables that they offered for sale, as well as how to properly dispose of the commercialized fruits and vegetables. It was verified that part of the garbage produced at the fair, corresponded to food not sold on the spot. Therefore, knowledge about the points mentioned above results in the offer of quality food for sale, generating a reduction in food waste and financial losses to marketers. Faced with this issue at the end of the work, a booklet was developed with all this information that was distributed, as a way of raising awareness and offering knowledge to marketers.